Synthesis of Copper Oxide from HKUST-1 and Its Applications for Removal of Congo Red - Maulidah, Izzah; Patah, Aep (Jurnal Riset Kimia, 2026)
This study presents research findings on the synthesis and characterization of HKUST-1 and derived-copper oxide materials, with significant practical implications. The HKUST-1 was synthesized using the solvothermal method at 100 °C for 10 hours using copper nitrate trihydrate (Cu(NO3)2∙3H2O) as the metal ion and trimesic acid as the ligand. The various copper oxides, CuO (air), Cu/Cu2O/C (Ar), and CuO (Ar/O2) were produced through pyrolysis from HKUST-1 at 600 °C for 8 hours. X-ray Diffraction (XRD) analysis confirmed the characteristic peaks of HKUST-1 and the other copper oxides. Pyrolysis under argon yielded a Cu/Cu2O/C (Ar) mixture instead of CuO. Fourier Transform Infrared (FTIR) spectroscopy showed consistent absorption bands while Scanning Electron Microscopy (SEM) revealed that HKUST-1 and derived HKUST-1 copper oxides had an octahedral crystal morphology. UV-DRS analysis demonstrated that CuO derived HKUST-1 exhibited smaller band gap as compared to the pure CuO sample. Adsorption tests with a 50 ppm Congo Red (CR) solution showed that all materials reached optimal adsorption at 60 minutes, with Cu/Cu2O/C (Ar) achieving the highest capacity of 95,52 mg/g. In photocatalysis tests, CuO (Ar/O2) removed 53% of contaminants, outperforming commercial CuO at 29%. The Cu/Cu2O/C (Ar) composite demonstrated the highest removal rate at 99%, indicating its potential for practical applications.